ChemInform Abstract: An Unsymmetrical Iron Catalyst for the Asymmetric Transfer Hydrogenation of Ketones. Issue 42 (October 2015) - Smith, Samantha A. M.; Morris, Robert H.
Abstract The new iron(II)(Ph2P‐NH‐N‐PCy2) complex possessing a dicyclohexylphosphino group trans to the NH group efficiently catalyzes the asymmetric transfer hydrogenation of prochiral ketones furnishing the corresponding alcohols with high enantioselectivity.